Mudanças de uso da terra na paisagem cultural. Caso de estudo : município de São Carlos, SP - Souza, Imyra Maíra Martins de (2015)
The complexity and interaction of environmental problems have directed the landscape structure studies, which emphasizes broad spatial scales related to ecological effects of spatial patterns of the ecosystems. Changes in the landscape result in the impairment of natural capital and ecosystem functions that regulate or modulate the goods and services provided to human wellbeing, supported by the properties and/or physical, biological or chemical processes that occur in natural systems. For understanding the trajectories of natural and anthropogenic processes of landscape, many studies have addressed the models based on land use and land cover dynamics, which reflect the potential of the landscape transformation and thus assess implications for environmental sustainability scenario to over time. Thus, this thesis aims to draw up scenarios and projections of landscape patterns resulting from the interaction society and nature, based on structural indicators of the municipality of San Carlos landscape, basing the discussion on changes in natural capital in sustainable capacity in provide ecosystem services.